2014
DOI: 10.5573/jsts.2014.14.5.594
|View full text |Cite
|
Sign up to set email alerts
|

Pixel Circuit with Threshold Voltage Compensation using a-IGZO TFT for AMOLED

Abstract: Abstract-A threshold voltage compensation pixel circuit was developed for active-matrix organic light emitting diodes (AMOLEDs) using amorphous indium-gallium-zinc-oxide thin-film transistors (a-IGZO-TFTs). Oxide TFTs are n-channel TFTs; therefore, we developed a circuit for the n-channel TFT characteristics. The proposed pixel circuit was verified and proved by circuit analysis and circuit simulations. The proposed circuit was able to compensate for the threshold voltage variations of the drive TFT in AMOLEDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…As a result, the deteriorated picture quality in the panel stands out severely at the extremely low luminance and then vendors of the AMOLED panel have confronted the large yield drop. To solve these problems, some researches that propose new internal [16][17][18][19][20][21][22][23] or external [13,24] compensation circuits or improving uniformity of TFT and OLED processes [25,26] have been reported. In other ways, researches suggesting an improving operation method for the reduction of the current sensitivity [27] or have proposed the screening method during the processes [28,29].…”
Section: Contact Hyun Jae Kimmentioning
confidence: 99%
“…As a result, the deteriorated picture quality in the panel stands out severely at the extremely low luminance and then vendors of the AMOLED panel have confronted the large yield drop. To solve these problems, some researches that propose new internal [16][17][18][19][20][21][22][23] or external [13,24] compensation circuits or improving uniformity of TFT and OLED processes [25,26] have been reported. In other ways, researches suggesting an improving operation method for the reduction of the current sensitivity [27] or have proposed the screening method during the processes [28,29].…”
Section: Contact Hyun Jae Kimmentioning
confidence: 99%
“…To reduce the Vth variation, additional compensation circuits are generally used. However, it requires additional elements and access to the driver TFT within the pixel cell, which leads to a complicated and big pixel cell size [10][11][12][13][14][15][16][17]. On the other hand, it was reported that the ferroelectric field effect transistor (FeTFT) enables the Vth to control and memorize the changed states of a transfer curve, which is the reconfigurable and non-volatile memory behavior [18].…”
Section: Introductionmentioning
confidence: 99%
“…Flexible organic light-emitting diode displays have received considerable attention in the past decades due to its massive potential in lightweight, wearable, and deformable displays. Since organic light-emitting diode displays are current-controlled display devices, , low-temperature polycrystalline silicon (LTPS) , as well as amorphous indium–gallium-zinc oxide (a-IGZO), have been applied as a backplane technology because of its excellent current driving ability. However, it suffers from the nonuniformity of the transistors in displays such as the mobility and the threshold voltage.…”
Section: Introductionmentioning
confidence: 99%